INITIAL STUDY ON THE POSSIBILITY OF GREENHOUSE GAS EMISSIONS FROM COASTAL WETLANDS IN HAI PHONG - Nam, Le Van (Vietnam Journal of Marine Science and Technology, 2016)
Total greenhouse gas emissions from some types of Hai Phong’s wetlands are 2,886,251 tonnes CO2e/year, converted from CO2, CH4 and N2O. In which, emissions from mangrove, aquaculture, paddy fields and permanent wetlands are 18,025 tonnes CO2e/year, 199,380 tonnes CO2e/year, 421,956 tonnes of CO2e/year 2,246,890 tonnes CO2e/year.